Nato's Alleged Violations Of UN Security Council Resolutions In Libya - Fikry Latukau; Muhammad Zacky (Universitas Internasional Batam, 2025)
The Security Council resolution against Libya emphasises that any State has the right to intervene if it commits crimes against humanity or causes civilian casualties. This paper examines the issue of Security Council intervention through NATO against Libya in relation to international criminal law. The results show that the Security Council has the right to intervene but in reality the intervention carried out by NATO is not in accordance with the resolution issued by the Security Council. The fact that NATO's actions have caused civilian casualties and an increase in the number of refugees leaving Libya to save themselves.